ВЛИЯНИЕ КОМПЛЕКСНОЙ ТЕРАПИИ С ПРИМЕНЕНИЕМ СУЛОДЕКСИДА НА ФУНКЦИОНАЛЬНОЕ СОСТОЯНИЕ ПЕЧЕНИ БОЛЬНЫХ ПСОРИАЗОМ - Тошев, Сухроб Уктамжон угли; Абдуллаев, Хасан Давлатович; Маматов, Жахонгир Мавлонович (Educational Research in Universal Sciences, 2024)
Psoriasis is a chronic inflammatory skin disease characterized not only by epidermal manifestations, but also by systemic associated changes. One aspect that requires attention in the context of psoriasis is its impact on liver function. Associated events such as metabolic syndrome, inflammation, and drug use may have a negative impact on liver function in patients with psoriasis.